Molecular correlates for HPV-negative head and neck cancer engraftment prognosticate patient outcomes - Matthew Waas; Christina Karamboulas; Benson Z. Wu; Shahbaz Khan; Stephanie Poon; Jalna Meens; Meinusha Govindarajan; Amanda Khoo; Salvador Mejia-Guerrero; Annie Ha; Lydia Y. Liu; Kevin C. J. Nixon; et al. (Nature Communications)
Abstract There is a pressing need to improve risk stratification and treatment selection for HPV-negative head and neck squamous cell carcinoma (HNSCC) due to the adverse side effects of treatment. One of the most important prognostic features is lymph nodes involvement. Previously, we demonstrated that tumor formation in patient-derived xenografts (i.e. engraftment) was associated with poor clinical outcomes in patients with HPV-negative HNSCC. However, assessing engraftment is challenging in clinical settings. Here, we perform transcriptomic and proteomic profiling of 88 HNSCC patients and find the relationship between engraftment and clinical outcomes is recapitulated by molecular phenotype. We identify LAMC2 and TGM3 as candidate prognostic biomarkers and validated their utility in an independent cohort containing 404 HPV-negative HNSCC patients. Strikingly, these markers significantly improve prediction of outcomes beyond nodal status alone and can significantly stratify patients without any nodal involvement. Overall, our study demonstrates how the molecular characteristics of engraftment can inform patient prognostication.